Norovirus Persistence in Oysters to Prolonged Commercial Purification - Roberta Battistini; Chiara Masotti; Valeria Listorti; Elisabetta Suffredini; Cristiana Maurella; Aitor Garcia-Vozmediano; Erica Costa; Francesco Iacona; Mino Orlandi; Carlo Ercolini; Laura Serracca (Pathogens, 2021)
Depuration is generally the main treatment employed for bivalve mollusks harvested from contaminated sites. Commercial depuration has demonstrated to be effective for removal of bacterial pathogens, although it probably provides only limited efficacy against human enteric viruses. We evaluated the quantitative reduction of norovirus (NoV) genogroups I and II in naturally contaminated oysters after 1, 4, and 9 days of depuration. The process was conducted in an authorized depuration plant, and NoV concentration was determined by RT-qPCR according to ISO 15216-1:2017 method. Regardless of the NoV genogroup, our results showed no significant reduction in NoV concentration after 1 day of depuration. Higher mean reduction (68%) was obtained after 4 days of treatment, while no further increase was observed after 9 days. Overall, reduction was highly variable, and none of the trials showed statistically significant reduction in NoV RNA concentration at the end of each depuration period. Indeed, NoV concentration remained high in 70% of samples even after 9 days of depuration, with values ranging between 4.0 × 102 and 2.3 × 104 g.c./g. These results indicate that an extension of commercial depuration time does not appear to be effective for reducing or eliminating NoV in oysters.